Fear of writing in public: a case study (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This article aims to present interventions in problematic behaviors of a 38-year-old patient, who reported experiencing fear of writing in public. Based on reports and patient records, cognitive-behavioral therapist might describe the contingencies of which his behavior was function, and thus taught to the patient, management of ways this anxiety. Having a diagnosis, social phobia, with circumscribed framework of fear of writing in public, the patient underwent cognitive-behavioral techniques to acquire a new repertoire to respond adequately to aversive situations.
Keywords: fear of writing in public; social phobia; cognitive-behavioral techniques